(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: in Uruguay, the proportion of low weight births (LBW) remains close to 8%. It is a challenge to achieve adequate growth and development focused on preventing diseases in the medium and long term for the case of this group. Objective: analyze the growth rate and nutritional aspects of a cohort of newborns (NB) with LBW since they were discharged from the hospital and until 12 months of corrected age (CA). Methodology: descriptive, prospective study of NBs with LBW of the neonatal ward of the Manuel Quintela Maternity Hospital, between January 1 and December 31, 2015. We excluded carriers of congenital malformations and surgical pathology at birth and assessed weight, length and cranial perimeter at discharge, and at 5, 9 and 12 months of CA. The growth rate was analyzed using z-score and Δz-score adjusted to CA in WHO curves. Nutritional contribution was estimated in each check-up and associations were explored between changes in the growth curve and the degree of adequacy of the estimated caloric intake. Results: 31 newborns participated in the test: 7 newborns had a birth weight of <1.500 g and ≥1.500 g: 24. Mean Gestational Age (GA) 32.5 weeks (range 25-39), one term and 30 preterm newborns: extreme 2, very premature 9, and moderate 19. Regarding birth weight according to gestational age, 21 were appropiate for gestational age (AGA), 7 small for gestational age (SGA) and 3 large for gestational age (LGA). The 26 children completed the 3 scheduled check-ups. In the 1st check-up, 15 children had been able to maintain the growth trend, in 8 of them it had decreased and in 8 it had accelerated; in the 2nd check-up 9 of them maintained their growth rate, 9 decreased it and 12 of the newborns increased it; and in the 3rd check-up, the trend remained steady for 9 of them , it decreased for 7 of them and it increased for 10 of them. The number of children who at the end of the follow-up maintained the same growth trend they had at birth decreased, despite the increase in the growth trend of those with a more accelerated growth. At the time of the 3rd check-up it was found that only 9 children maintained the growth trend they had at birth and the rest, (17), changed trends, which resulted in a significant gap. We did not find links life between the growth rate and the energy characteristics of the supplementary food they received in the 10 patients who had increased their growth rate in their first year of life. Conclusions: we observed problems regarding the growth rate of children with LBW during the first year of life. A significant proportion showed accelerated growth, which is a risk factor for obesity and chronic non-communicable diseases. It is necessary to research the causes of these alterations, especially regarding their feeding practices in order to develop strategies for their prevention.